A Liturgy of Grief : a pastoral commentary on Lamentations - Allen, Leslie C. (Grand Rapids, Mich. : Baker Academic, 2011)
Allen, an experienced scholar and hospital chaplain, is the first to use the Old Testament book of Lamentations to throw light on grief, and to use contemproray examples and discussions of grief to throw lights on Lamentations.
Includes bibliographical references (p. 180-190) and index.
Keywords: Bible. -- Commentaries; Grief -- Religious aspects -- Christianity; Pastoral care